MEDIA DISPLAY DARI BAHAN LIMBAH AN-ORGANIK SEBAGAI MEDIA PEMBELAJARAN IPA KELAS V DI SD N 2 BANYUMUDAL - Wanandi, Achmat Iwan; Suyoto, Suyoto; Ngazizah, Nur (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This research aims to (1) develop display media from inorganic waste materials, (2) determine the validity, practicality and effectiveness of developing display media from inorganic waste materials. This research uses research and development methods with the ADDIE model (analysis, design, development, implementation, and evaluation). The subjects of this research were class V students at SD Negeri 2 Banyumudal. Data collection techniques use interview methods, test methods, questionnaire methods, and documentation methods. The learning instruments are in the form of a syllabus and teaching modules, while the assessment instruments are validation sheets from media experts, materials and practitioners, and student response questionnaires. Based on the research results, it can be concluded that (1) a product is produced in the form of display media which can be used as reference material and learning media, (2) the validity of the display media results in an average of 3.6 with valid criteria, (3) the practicality of the display media is seen from Student responses at the extensive trial stage received a percentage of 89.55% in the very practical category. (4) the effectiveness of display media seen from the evaluation value at the extensive trial stage received an average of 87.2 in the very effective category. So, it is concluded that display media made from inorganic waste materials can be categorized as valid, practical and effective as a learning resource for elementary school learning.